Pata Dela: Identitas Budaya Dalam Mendukung Toleransi Dan Kerukunan Antar Umat Beragama - Betu, Silverius (Unika Santu Paulus Ruteng, 2023)
Tolerance and harmony between religious communities is very important and has been fought for from generation to generation. Indonesia is a pluralistic society Therefore, tolerance and harmony are needed, which are understood, lived, and implemented in living together. Pata Dela in the Reba traditional ceremony is one of the local wisdom of the Ngada community and upholds the values ??of tolerance and harmony. Pata Dela is the message for the Ngada people from their ancestors to live side by side in peace, see each other as brothers, and be fair in living together. Pata Dela is not just an ancestral message delivered every year in the traditional Reba ceremony but also becomes the cultural identity of the Ngada people, which is heard, contemplated, internalized, and implemented in everyday life. These values ??of local wisdom need to be raised and disseminated because social media is intensively exposing hate speech and sentiments motivated by Sara, strengthening primordial attitudes, actions, and intolerance. Hopefully, this article can increase the values ??of tolerance and harmony in society and strengthen the nation's unity and integrity.